TRANSFORMATION OF UKRAINIAN INSTITUTIONAL SYSTEM IN THE CONTEXT OF EUROPEAN DEVELOPMENT VECTOR - Babukh, Ilona; Pochenchuk, Galyna (Izdevnieciba “Baltija Publishing", 2016)
The article deals with the peculiarities of institutional system, wich was formed in Ukraine. The research identifies that the country institutional system is crucial for the effective functioning of a particular model of economic development. Socio-economic systems of different countries differ primarily by specific features of their institutional environments. The European choice remains the driving force of institutional change in Ukraine. Estimation of present levels of institutional development is hold on the use of international quality indices of institutional development and their individual components, as well as the results of sociological research, got from open sources. The results of the research showed that consequence of previous transformation processes become to the emergence, dissemination and consolidation of inefficient institutions and a considerable matter of their dysfunctionality. Such condition is confirmed by both the indicators of indices of institutional environment quality and national sociological researches. Consequently the reforming of Ukrainian institutional structure requires a number of reforms, without copying the institutional structure of Western countries, and taking into account the national differences and peculiarities of the historical development of the country.